Balagtasan Beyond Balagtas: Debate Poetry, a Filipino Tradition - Carmelo D. Nadera Jr, Victor Emmanuel; Mooney-Singh, Chris (SARE: Southeast Asian Review of English, 2019)
This paper charts the history, influence, and contemporary practice of Balagtasan, a poetic performance tradition that pays homage to the â€œFilipino Shakespeare,â€ Francisco Balagtas (born, 1788), predating what is known as â€œfliptopâ€ or the Filipino rap battle. For 95 years, Balagtasan has debated and explored the social and political terrain and, in so doing, broadened awareness and deeper discussion of important Filipino issues. The authors also consider the impact of competitive jousting between pairs of poets as a grassroots form that has built community throughout an archipelago of 7,107 islands, speaking from rural and urban centres of population across the expanse of water and sky through elegant cultural engagement in Tagalog, the Philippine language.